Governing the city. - (:unkn) unknown (My University, 2015)
Regions and cities are on the front lines in the battle to achieve inclusive growth They are where policies meet people in their daily lives. This second edition of the OECD Regional Outlook comes at a time when many regions and cities are still trying to bounce back from the financial crisis of 2008. Inequalities between places and among populations remain entrenched. Citizens are calling for a more inclusive form of growth. They want a more comprehensive approach to well-being, with policies that address daily concerns in people's lives, from ready access to jobs and education to safe and healthy environments and efficient and effective health care for young and old. Citizens also expect and demand that regions and cities be made as resilient as possible in the face of economic and demographic developments and natural disasters. Part I of this OECD Regional Outlook makes the case for the contribution of regions and cities to overall economic performance. It describes the main trends at the regional and city level, notably on increasing income disparities, and provides a comprehensive overview of the institutional setting of regional policies across OECD countries and of ongoing territorial reforms. To address these challenges and opportunities, Part II responds directly to the call by ministers for OECD data and policy guidance on topics of priority for their national agendas. It addresses the issues involved in the management of public investment and the challenges of fitting policies to places. Policy makers need a clear vision of these realities to respond at the appropriate geographic scale, which does not always coincide with municipal and regional administrative boundaries. The Policy Forum, Part III of this outlook, gathered key policy makers.
Keywords: Stadtplanung; Stadtentwicklungsplanung; Großstadt; Stadtregion; Stadtentwicklung; Wirtschaftsentwicklung; Stadtwachstum; Fallstudie; Internationaler Vergleich; Governance